An Aeration Pressure, Plant Spacing, And Dissolved Oxygen For Growth Of Lettuce (Lactuca Sativa L.) Plants In Floating Hydroponics - Puspitahati puspitahati; Fidel Harmanda Prima; Nurul Izzah; Nikita Prettisha (Jurnal Penelitian Pertanian Terapan, 2024)
The successful growth of lettuce plants in floating hydroponics is controlled by the availability of oxygen and the level of plant density.  Dissolved oxygen in water is controlled by the aeration pressure provided in hydroponics. This research aims to determine The impact of aeration pressure on the growth of lettuce (Lactuca sativa L) in a floating hydroponic system, considering different planting spacings. The research employed a Randomized Block Factorial Design (RAKF), incorporating two treatment factors: plant spacing (Factor A) with two different levels, and aeration pressure (Factor B) with three different levels. Each combination was replicated three times. And oxygen linear regression analysis for dissolved (Dissolved Oxygen) and aeration pressure.  The conclusion of the research showed that The conclusions of this research were The highest production of lettuce was achieved with treatment A2B3, using a planting distance of 30 cm and aeration pressure of 16 kPa, resulting in a total fresh weight of the plants of 82.89 g, Lettuce planted at a spacing of 30 cm outperformed lettuce planted at 20 cm in terms of canopy width, root length, and total fresh weight, 3.The aeration pressure increases, the concentration of dissolved oxygen in the water also increases, the canopy width, root length, and total fresh weight of lettuce. The average dissolved oxygen ranged from 7.17 to 7.22 mg/l, so the aeration pressure correlates with increased dissolved oxygen levels, suggesting that higher aeration pressure correlates with increased dissolved oxygen levels. The Suggestion was Further research should be conducted on the appropriate size of the nutrient solution reservoir concerning the aeration pressure applied.